(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Touch DNA is referred to as DNA that is recovered from very few cells (usually 6-7 in number) transferred from an individual to another object by means of contact through the skin.For extraction of touch DNA, careful handling anda very sensitive extraction technique is required. The objective of this study was to determine minimum fingerprints required for amplifiable DNA along with best method to isolate the DNA from fingerprints. The DNA sample was taken into 4 gradations, i.e., 6 fingerprints, 4 fingerprints, 2 fingerprints and single thumb print. 10 samples from each gradation were taken for each method (organic, chelax100 and commercial kit). Quantification of DNA was done with real time PCR.As the area of swabbing/ number of fingerprints decreases, the chances of getting ample DNA for profiling decreases. All the three methods provide DNA optimal for profiling with 6 and 4 fingerprints in 70% samples, which decreases gradually and chances of getting a DNA profile from a single fingerprint is very rare. Among the three extraction techniques organic method is found be more consistent from single fingerprint followed by DNA IQ systems kit method. The variation in the amount of DNA of each sample is due to different physiological conditions of the subjects.